16.2k views
1 vote
Sharon tried to solve an equation step by step.

\qquad\begin{aligned} 9&=-3(e-2)\\\\ \\ 9&=-3e+6&\green{\text{Step } 1}\\\\ \\ 15&=3e&\blue{\text{Step } 2}\\\\ \\ 5&=e&\purple{\text{Step } 3}\\\\ \end{aligned}

9

9

15

5




=−3(e−2)

=−3e+6

=3e

=e




Step 1

Step 2

Step 3




Find Sharon's mistake.

2 Answers

6 votes

Answer:

Step 2

Explanation:

Khan academy inequalities 7th grade math unit test

User Doris Chen
by
5.1k points
5 votes

Answer:

Sharon made a mistake in step 2.

Explanation:

Sharon tried to solve an equation step by step.


\qquad\begin{aligned} 9&=-3(e-2)\\\\ \\ 9&=-3e+6&\green{\text{Step } 1}\\\\ \\ 15&=3e&\blue{\text{Step } 2}\\\\ \\ 5&=e&\purple{\text{Step } 3}\\\\ \end{aligned}

The correct steps are:

The given equation is


9=-3(e-2)

Step 1: Using distributive property we get


9=-3e-3(-2)


9=-3e+6

Step 2: Subtract 6 from both sides.


9-6=-3e+6-6


3=-3e

Step 3: Divide both sides by -3.


(3)/(-3)=(-3e)/(-3)


-1=e

Therefore, Sharon made a mistake in step 2.

User Shadonar
by
5.3k points